2010
DOI: 10.1111/j.1365-2524.2010.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation during pregnancy: the influence of partners, family and friends on quitters and non-quitters

Abstract: This research compared pregnant quitters' and non-quitters' accounts of how partners, family and friends influenced their smoking cessation attempts. Qualitative secondary data analysis was carried out on a purposive sample of motivational interview transcripts undertaken by research midwives with pregnant women as part of SmokeChange, a smoking cessation intervention. Interviews with all quitters in the intervention group (N=12) were analysed comparatively with interviews from a matched sample of non-quitters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 82 publications
2
30
0
11
Order By: Relevance
“…There is, however, only scarce epidemiological evidence for this assumption. While two studies suggested that potential effects might be stronger in male children (39,40), others showed similar odds ratios for overweight and obesity in male and female offspring (5,41). The results from the latter studies are well in accordance with those from our previous study (34) and the present one, in neither of which we found indications of sex-specific effect modifications.…”
Section: Discussionsupporting
confidence: 92%
“…There is, however, only scarce epidemiological evidence for this assumption. While two studies suggested that potential effects might be stronger in male children (39,40), others showed similar odds ratios for overweight and obesity in male and female offspring (5,41). The results from the latter studies are well in accordance with those from our previous study (34) and the present one, in neither of which we found indications of sex-specific effect modifications.…”
Section: Discussionsupporting
confidence: 92%
“…The pregnant women think that nicotine consumption can make their children more sensitive to dependence, which was also described by Woolston (2006). Koshy et al (2010), and the experiences of the participants in the interviews in Estonian three women`s clinics, it appeared that the pregnancy is a significant motivator for quitting smoking, but smokers had an opinion that the child of the woman who is smoking during pregnancy will weigh less and thus, it will be easier to give a birth. Some women knew that being in smoky rooms affects the health as well as smoking.…”
Section: Subcategory: Negative Experiences Linked To Smoking Cessationmentioning
confidence: 99%
“…According to this understanding, smoking is allowed until the birth of a child and this is not condemnable , which was also proved by the research for fathers, described by Giglia et al (2006), where most fathers stopped smoking after the birth of a child explaining that with a feeling that until the birth, the expected child was not real yet. According to the experiences of the participants in the interviews in three women`s clinics, living together with a smoking partner is the main inhibiting factor in smoking cessation permitting access to cigarettes and promoting to make a comfortable environment for smoking, and by Koshy et al (2010) and Tombor et al (2010), smoking is a common way to spend time together. Factors that inhibit smoking cessation were brought out by the participants: when quitting smoking you have to give up your good mood, tranquillity, sweets and coffee.…”
Section: Subcategory: Negative Experiences Linked To Smoking Cessationmentioning
confidence: 99%
See 2 more Smart Citations